The French exile of Alejandro Lerroux and his relationship with Francesc Ferrer Guàrdia (1908–1909). - Esculies, Joan (Journal of Iberian & Latin American Studies, 2025)
In the spring and summer of 1908, Alejandro Lerroux lived in exile in Paris before embarking on his famous trip to Argentina. The biographical studies of the Republican leader barely stop to talk about this period. However, the nine months he spent in the French capital are key to understanding his relationship with Francesc Ferrer Guàrdia and his subsequent decision not to get involved in the campaign in favour of the educator's innocence, when he was arrested for the events of the Tragic Week and later executed by firing squad in October 1909. Based on unpublished documentation, this article tries to remedy this biographical gap, and details Lerroux's political activities in France and his relationship with Ferrer during this period.